Recent Advances in Natural Computing Selected Results from the IWNC 8 Symposium - Suzuki, Yasuhiro; Hagiya, Masami (Mathematics for Industry, 2016)
This book highlights recent advances in natural computing, including biology and its theory, bio-inspired computing, computational aesthetics, computational models and theories, computing with natural media, philosophy of natural computing, and educational technology. It presents extended versions of the best papers selected from the "8th International Workshop on Natural Computing" (IWNC8), a symposium held in Hiroshima, Japan, in 2014. The target audience is not limited to researchers working in natural computing but also includes those active in biological engineering, fine/media art design, aesthetics, and philosophy.